2008
DOI: 10.1016/j.ajhg.2008.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the GIGYF2 (TNRC15) Gene at the PARK11 Locus in Familial Parkinson Disease

Abstract: The genetic basis for association of the PARK11 region of chromosome 2 with familial Parkinson disease (PD) is unknown. This study examined the GIGYF2 (Grb10-Interacting GYF Protein-2) (TNRC15) gene, which contains the PARK11 microsatellite marker with the highest linkage score (D2S206, LOD 5.14). The 27 coding exons of the GIGYF2 gene were sequenced in 123 Italian and 126 French patients with familial PD, plus 131 Italian and 96 French controls. A total of seven different GIGYF2 missense mutations resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
135
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(140 citation statements)
references
References 54 publications
1
135
2
2
Order By: Relevance
“…Another study of North American and Portuguese PD cases found two of these mutations, but only in healthy persons [256], and a study of primarily Italian cases found no mutations [257], casting doubt whether the GIGYF2 is a causative PD gene. In a large sample of US and Norwegian PD cases (in total 1,139 cases), one of the originally reported [172] mutations was identified in three US sporadic cases, but none of the other mutations were found [258].…”
Section: Park11mentioning
confidence: 95%
See 2 more Smart Citations
“…Another study of North American and Portuguese PD cases found two of these mutations, but only in healthy persons [256], and a study of primarily Italian cases found no mutations [257], casting doubt whether the GIGYF2 is a causative PD gene. In a large sample of US and Norwegian PD cases (in total 1,139 cases), one of the originally reported [172] mutations was identified in three US sporadic cases, but none of the other mutations were found [258].…”
Section: Park11mentioning
confidence: 95%
“…To date (2010), 11 genes and an additional 3 genetic loci have been associated with PD [168][169][170][171][172][173][174][175][176][177][178][179][180][181][182][183][184]; two additional loci await to be confirmed [185,186]. The PD genes and loci are described in Table 4.…”
Section: Genes and Loci In Familial Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…Cependant, le rôle spécifique de la protéine adaptatrice Grb10 dans le développement neurologique a déjà été suggéré par la découverte de mutations pathogènes dans le syndrome de Silver -Russell, qui associe un retard de croissance intra-utérin et un retard du développement psychomoteur ou du langage [13]. Notre étude du gène GIGYF2 par séquençage direct dans 249 cas familiaux (italiens et français) de la maladie de Parkinson et 227 témoins nous a permis d'identifier une mutation (faux-sens) du gène GIGYF2 chez 6 % des sujets atteints de maladie de Parkinson [14]. D'autre part, nous avons pu observer une importante variabilité de type insertion et délé-tion de codons glutamine (Glu).…”
Section: Ide (Insulin Degrading Enzyme) Et Maladie D'alzheimerunclassified
“…The discovery of genetic forms of PD, and the subsequent identification of the causative genes behind these cases, has provided us with important signposts towards research areas that we need to focus on in this disease. Recently, a putative thirteenth region of the genome has been identified, which is known to code for the protein TNRC15 (Lautier, 2008). It is likely that other such genes will be identified in the future.…”
Section: What Does the Future Hold?mentioning
confidence: 99%